Lycopene alleviates hepatic ischemia reperfusion injury via the Nrf2/HO-1 pathway mediated NLRP3 inflammasome inhibition in Kupffer cells - Xue, Rong (Ann Transl Med, 2021)
BACKGROUND: Lycopene is a naturally occurring carotenoid found in many fruits and vegetables, which has antioxidant effects. Although lycopene’s protective effect has been observed on ischemia reperfusion (IR) injury in different organs, the effect of lycopene on Kupffer cells (KCs) has not been clearly elucidated in IR-induced acute hepatic inflammatory injury. METHODS: Mice were administered with either olive oil (10 mL/kg body weight) as the control or lycopene (20 mg/kg body weight) by gavage for 2 weeks before undergoing hepatic IR injury. RESULTS: In this study, we observed that the levels of aspartate aminotransferases (AST), alanine aminotransferase (ALT), and the percentages of hepatocellular apoptosis in mice pretreated with lycopene were significantly lower than control mice. Lycopene inhibited F4/80+ macrophage and Ly6G+ neutrophil accumulation, which further decreased the levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin 6 (IL-6). Interestingly, lycopene induced increased autophagy in KCs, which was evidenced by elevated autophagosomes and the increased protein level of LC3B. In these KCs, lycopene-induced upregulation of autophagy inhibited NOD-like receptor family pyrin domain-containing 3 protein (NLRP3) inflammasome activation, which was demonstrated by the reduced mRNA and protein levels of NLRP3, cleaved caspase-1, an apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC), and IL-1β. Furthermore, 3-methyladenine, an autophagy inhibitor, abolished lycopene’s inhibitory effect on the NLRP3 inflammasome in KCs, which led to increased hepatic IR injury. Intriguingly, we identified that the protein levels of nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase 1 (HO-1) were elevated in KCs isolated from IR-stressed mice pretreated with lycopene. Nrf2-siRNA or HO-1-siRNA could block the autophagy activation enhanced by lycopene in KCs, resulting in the activation of the NLRP3 inflammasome and aggravated hepatic IR injury. CONCLUSIONS: Our findings demonstrated that lycopene promoted Nrf2/HO-1 pathway activation and further suppressed the NLRP3 inflammasome via enhancing KC autophagy, which alleviated hepatic IR injury.